Coformulated bictegravir, emtricitabine, and tenofovir alafenamide versus dolutegravir with emtricitabine and tenofovir alafenamide, for initial treatment of HIV-1 infection (GS-US-380–1490): a randomised, double-blind, multicentre, phase 3, non-inferiority trial. Issue 10107 (4th November 2017) - Sax, Paul E; Pozniak, Anton; Montes, M Luisa; Koenig, Ellen; DeJesus, Edwin; Stellbrink, Hans-Jürgen; Antinori, Andrea; Workowski, Kimberly; Slim, Jihad; Reynes, Jacques; Garner, Will; Custodio, Joseph; et al.
Summary: Background: Integrase strand transfer inhibitors (INSTIs) coadministered with two nucleoside or nucleotide reverse transcriptase inhibitors (NRTIs) are recommended as first-line treatment for HIV, and coformulated fixed-dose combinations are preferred to facilitate adherence. We report 48-week results from a study comparing initial HIV-1 treatment with bictegravir—a novel INSTI with a high in-vitro barrier to resistance and low potential as a perpetrator or victim of clinically relevant drug interactions—coformulated with the NRTI combination emtricitabine and tenofovir alafenamide as a fixed-dose combination to dolutegravir administered with coformulated emtricitabine and tenofovir alafenamide. Methods: In this randomised, double-blind, multicentre, placebo-controlled, non-inferiority trial, HIV-infected adults were screened and enrolled at 126 outpatient centres in 10 countries in Australia, Europe, Latin America, and North America. Participants were previously untreated adults (HIV-1 RNA ≥500 copies per mL) with estimated glomerular filtration rate of at least 30 mL/min. Chronic hepatitis B virus or hepatitis C co-infection was allowed. We randomly assigned participants (1:1) to receive oral fixed-dose combination bictegravir 50 mg, emtricitabine 200 mg, and tenofovir alafenamide 25 mg or dolutegravir 50 mg with coformulated emtricitabine 200 mg and tenofovir alafenamide 25 mg, with matching placebo, once a day for 144 weeks. Investigators, participants, study staff, and those assessing outcomes were masked to treatment group. All participants who received at least one dose of study drug were included in primary efficacy and safety analyses. The primary endpoint was the proportion of participants with plasma HIV-1 RNA of less than 50 copies per mL at week 48 (US Food and Drug Administration snapshot algorithm), with a prespecified non-inferiority margin of −12%. This study is registered withClinicalTrials.gov, numberNCT02607956 . Findings: Between Nov 11, 2015, and July 15, 2016, 742 participants were screened for eligibility, of whom 657 were randomly assigned to treatment (327 with bictegravir, emtricitabine, and tenofovir alafenamide fixed-dose combination [bictegravir group] and 330 with dolutegravir plus emtricitabine and tenofovir alafenamide [dolutegravir group]). 320 participants who received the bictegravir regimen and 325 participants who received the dolutegravir regimen were included in the primary efficacy analyses. At week 48, HIV-1 RNA <50 copies per mL was achieved in 286 (89%) of 320 participants in the bictegravir group and 302 (93%) of 325 in the dolutegravir group (difference −3·5%, 95·002% CI −7·9 to 1·0, p=0·12), showing non-inferiority of the bictegravir regimen to the dolutegravir regimen. No treatment-emergent resistance to any study drug was observed. Incidence and severity of adverse events were similar between groups, and few participants discontinued treatment due to adverse events (5 [2%] of 320 in the bictegravir group and 1 [<1%] 325 in the dolutegravir group). Study drug-related adverse events were less common in the bictegravir group than in the dolutegravir group (57 [18%] of 320 vs 83 [26%] of 325, p=0·022). Interpretation: At 48 weeks, virological suppression with the bictegravir regimen was achieved and was non-inferior to the dolutegravir regimen in previously untreated adults. There was no emergent resistance to either regimen. The fixed-dose combination of bictegravir, emtricitabine, and tenofovir alafenamide was safe and well tolerated compared with the dolutegravir regimen. Funding: Gilead Sciences Inc.